Evaluasi Penerapan SIM-RS Menggunakan COBIT 5 pada RSUD Lawang - Gita Natalia Krisnawati; Sucipto Sucipto; Rina Firliana (Universitas Islam Balitar, 2019)
Information technology (IT) has become a crucial part for companies or institutions with enterprise scale. The problem in this research is the service of patients in RSUD Lawang has not been entirely done using the SIM-RS application directly. This study focuses on the implementation of the SIM-RS in Lawang District Hospital in providing health services to the community. This research standard uses COBIT 5 standard with APO 07 domain which discusses the preparation of HR in Lawang District Hospital, BAI 07 discusses readiness in obtaining new information systems (SIM-RS), and DSS 01 discusses procedural development and treatment of all forms operations, infrastructure, and facilities related to the information system used. The conclusions of this study are: (1) The level reached by the APO 07 domain is at level 1. This is due to the application of the SIM-RS in the Lawang District Hospital, which has a base practice but in the design of activities that have not been adequately monitored and evaluated and the work products that have not been applied, controlled, and maintained as appropriate. (2) The level achieved by the BAI 07 domain is at level 2. This is due to the application of the SIM-RS in Lawang District Hospital, which has a planned base of practice, is well monitored and evaluated. Its implementation is following agency needs. But related to the implementation process is still not following established standards. (3) The level achieved by the DSS 01 domain is at level 1. This is due to the application of the SIM-RS in Lawang District Hospital having a base practice. Still, in the design of activities, it has not been adequately monitored and evaluated, and the work products they have not been implemented, controlled, and maintained as should be.